Resolution of the Polish Sejm on the 80th Anniversary of the Volhynian Crime in its Socio-political and Historical Context - Głowacka, Katarzyna (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
In July 2023, Poland commemorated the 80th anniversary of the Genocide of Poles in Volhynia and Eastern Galicia – a crime committed by the Organization of Ukrainian Nationalists and the Ukrainian Insurgent Army during the Second World War. On 11 July, the Sejm of the Republic of Poland adopted a resolution honoring the memory of the victims. The Discourse-Historical Approach to Critical Discourse Analysis was applied to identify the discursive strategies pursued in the mentioned document. In discussing the strategies of nomination and predication, the author has used the analytical categories described by Theo van Leeuwen. The first section of the paper provides the extralinguistic, socio-political and historical context in which the analysed act emerged. The statements of other representatives of the state, which, on the eve of the anniversary celebrations, aroused the strongest – not necessarily positive – reactions, are also quoted therein. The article shows that the Sejm’s resolution of 11 July, like no other, respected the sensibilities of Borderland circles. However, the message it contained was at odds with the narrative articulated by the President of the Republic of Poland and the Polish Minister of Foreign Affairs. This discrepancy raised doubts whether there was deeper strategic thinking behind Polish historical policy. W lipcu 2023 r. Polacy upamiętnili 80. rocznicę ludobójstwa na Wołyniu i Galicji Wschodniej – zbrodni popełnionej przez Organizację Ukraińskich Nacjonalistów i Ukraińską Powstańczą Armię w trakcie II wojny światowej. 11 lipca Sejm Rzeczypospolitej Polskiej przyjął uchwałę, w której uczczono pamięć pomordowanych. Wykorzystując podejście dyskursywno-historyczne w ramach krytycznej analizy dyskursu autorka ukazała strategie dyskursywne, jakie realizowali twórcy tego dokumentu. Omawiając zastosowane strategie referencji oraz predykacji, odwołała się do kategorii analitycznych, które opisał Theo van Leeuwen. W otwierającej sekcji pracy zrekonstruowano kontekst zewnątrzjęzykowy, społeczno-polityczny i historyczny, w którym zaistniała analizowana wypowiedź. Przytoczono w niej również stwierdzenia innych przedstawicieli państwa polskiego, które w przededniu uroczystości upamiętniających 80. rocznicę zbrodni wołyńskiej wzbudziły najsilniejsze – niekoniecznie pozytywne – reakcje społeczne. Artykuł pokazuje, że uchwała Sejmu z 11 lipca (jak żadna inna) wpisała się we wrażliwość polskich środowisk kresowych. Przesłanie w niej zawarte nie pokrywało się jednak z narracją, jaką przyjął Prezydent Rzeczypospolitej Polskiej i polski Minister Spraw Zagranicznych. Zaobserwowany rozdźwięk prowokował pytania o to, czy za polską polityką historyczną stoi jakakolwiek głębsza myśl strategiczna.
Sejmowa uchwała upamiętniająca 80. rocznicę zbrodni wołyńskiej i jej społeczno-polityczny kontekst
Keywords: politics of memory; commemorative resolution; Volhynian Genocide; discourse-historical approach; discursive strategies; polityka pamięci; uchwały upamiętniające; ludobójstwo na Wołyniu; strategie dyskursywne; podejście dyskursywno-historyczne